IMPROVING STUDENTS' MATHEMATICAL SKILLS THROUGH PROBLEM-BASED LEARNING: A LITERATURE REVIEW PERSPECTIVE - Adi Asmara; Winda Ramadianti, Rahmat Jumri (International Journal of Teaching and Learning, 2025)
This study aims to explore the effectiveness of Problem-Based Learning (PBL) in improving students' mathematics skills through a literature review. PBL is a teaching method that places students at the centre of learning with an emphasis on solving contextual problems relevant to everyday life. The literature review showed that PBL can improve students' understanding of mathematical concepts and develop their critical and creative thinking skills. In addition, this method also strengthens students' collaborative and communication skills through structural group work. However, the successful implementation of PBL is influenced by several factors, such as the availability of resources, teachers' skills in implementing PBL, and the support of the school environment. To optimise learning outcomes, training for teachers and full support from all parties involved in the education process are required. The results of this study are expected to provide insights for educators about the potential of PBL as an effective method in improving students' mathematics skills.